The portuguese news industry’s perspectives and roles on the making of active citizens: readers’ skills to comment on the news - Brites, Maria José (2017)
This article investigates the news industry’s perceptions of letters to the editor and online comments in the context of the digital world and of the challenges journalists face. Using a sample of 11 semistructured interviews with journalists and ombudsmen in Portugal, we analyse the news industry’s views on readers’ ability to comment on the news and on the industry’s possible contributions to creating critical and engaged publics. The interviewees express concern about harmful behaviours in online environments and point to differences in online and offline contexts of participation. The results, however, do not reveal a proactive attitude in the news industry as the news professionals focus on their daily work activities as a form of media education and argue that schools and the public, instead, should take the lead in these activities. To support their statements, the interviewees cite factors such as the possibilities of digital culture, the promotion of media education, the need to foster a reciprocal relation between learning and the existing forms of journalism newsroom culture.